2021
DOI: 10.7759/cureus.17022
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy for the Treatment of Myocardial Infarction: How Far Are We Now?

Abstract: Myocardial infarction is one of the leading causes of death worldwide. Poor functional recovery of the myocardium is noticed after an event of myocardial infarction. Researchers and clinicians around the world have been engaged to regenerate the damaged human heart for a long time. Stem cell therapy is an exciting newer therapy to treat cardiovascular diseases. Various types of stem cells have been used to revive the damaged myocardium after myocardial infarction, and they have overall demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Studies on the use of CDCs for the treatment of acute myocardial infarction (MI) were found to improve left ventricular systolic function (LVSF) and reduce infarct scar size in various preclinical trials of coronary artery disease [37]. Results from the pre-clinical trials are somewhat consistent with outcomes found in clinical studies showing decreased scar mass, increased viable mass, and improved regional function consistent with therapeutic regeneration compared to the control group [31,38].…”
Section: Cardiosphere-derived Cells (Cdcs)mentioning
confidence: 73%
“…Studies on the use of CDCs for the treatment of acute myocardial infarction (MI) were found to improve left ventricular systolic function (LVSF) and reduce infarct scar size in various preclinical trials of coronary artery disease [37]. Results from the pre-clinical trials are somewhat consistent with outcomes found in clinical studies showing decreased scar mass, increased viable mass, and improved regional function consistent with therapeutic regeneration compared to the control group [31,38].…”
Section: Cardiosphere-derived Cells (Cdcs)mentioning
confidence: 73%
“…25 Although no teratomas were found during the structural evaluation, renal atrophy and mural thrombosis in the intracoronary Tx group caused the macaques to die before the end of the experiment. Although it has been reported that intracoronary Tx is effective, 26,27 studies with opposite conclusions have questioned its safety. 28 Our research on nonhuman primates suggested that when used, the intracoronary Tx strategy necessitates consideration of security risks.…”
Section: Discussionmentioning
confidence: 99%